2016
DOI: 10.1104/pp.16.00446
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis NATA1 acetylates putrescine and decreases defense-related hydrogen peroxide accumulation

Abstract: Biosynthesis of the polyamines putrescine, spermidine, and spermine is induced in response to pathogen infection of plants. Putrescine, which is produced from Arg, serves as a metabolic precursor for longer polyamines, including spermidine and spermine. Polyamine acetylation, which has important regulatory functions in mammalian cells, has been observed in several plant species. Here we show that Arabidopsis (Arabidopsis thaliana) N-ACETYLTRANSFERASE ACTIVITY1 (NATA1) catalyzes acetylation of putrescine to N-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 73 publications
9
53
0
Order By: Relevance
“…Instead, coronatine treated plants displayed increased ROS production after 24 h both in tomato (Ishiga et al, 2009) and in A. thaliana (Camanes et al, 2012) whole leaves. Recently it has been shown that coronatine strongly induces the expression of N-ACETYLTRANSFERASE ACTIVITY1 (NATA1), which leads to decreased defense-related H 2 O 2 accumulation through interference with polyamine metabolism (Lou et al, 2016). However, this effect occurs a few hours after coronatine treatment, while the effect of coronatine on stomata is very fast.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, coronatine treated plants displayed increased ROS production after 24 h both in tomato (Ishiga et al, 2009) and in A. thaliana (Camanes et al, 2012) whole leaves. Recently it has been shown that coronatine strongly induces the expression of N-ACETYLTRANSFERASE ACTIVITY1 (NATA1), which leads to decreased defense-related H 2 O 2 accumulation through interference with polyamine metabolism (Lou et al, 2016). However, this effect occurs a few hours after coronatine treatment, while the effect of coronatine on stomata is very fast.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the F. graminearum b-tubulin gene in seedling roots was measured using a previously published protocol (Lou et al, 2016). The primers used for quantitative reverse transcription polymerase chain reaction (qRT-PCR) detection of F. graminearum were FgTUB-qF293 (5 0 -ATGCTTCCAACA ACTATGCT-3 0 ) and FgTUB-qR411 (5 0 -AACTAGGAAACCC TGGAGAC-3 0 ), designed based on the F. graminearum strain PH-1 reference genome sequence (Cuomo et al, 2007).…”
Section: Fusarium Graminearum Gene Expression Measurement Mycotoxin mentioning
confidence: 99%
“…Surprisingly, a significant number of the metabolites with reduced levels under low light conditions or in cyp38 mutants are known biotic stress cues (Figure. 4F, Table S2): gluconic acid, which is derived from glucose, is associated with antifungal compound production [31]; glycerol-3-phosphate, which acts as a mobile factor for inducing systemic immunity in plants [32]; polyamines, including putrescine and spermidine, which regulate growth and also have important roles in modulating biotic and abiotic stress [33,34]; and linolenic acid, which is a precursor of the defense signaling molecules jasmonic acid and OPDA. Linolenic acid promotes lateral root development [35].…”
Section: Resultsmentioning
confidence: 99%